Respostas
respondido por:
0
Começando por uma regra de três
12 segundos - x minutos
60 segundos - 1 minuto
60x = 12
x = 12/60
x = 0,2 minutos*
1 hora - 60 minutos
y horas - 0,2 minutos*
60y = 0,2
y = 0,2/60
y = 0,003 horas.
12 segundos corresponde a 0,00333333 horas ou 0,003 horas
12 segundos - x minutos
60 segundos - 1 minuto
60x = 12
x = 12/60
x = 0,2 minutos*
1 hora - 60 minutos
y horas - 0,2 minutos*
60y = 0,2
y = 0,2/60
y = 0,003 horas.
12 segundos corresponde a 0,00333333 horas ou 0,003 horas
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás